Analisa Pembangkit Listrik Tenaga Ombak di Daerah Pesisir Jakarta Utara - Firyal, Faris; Susilowati, Sri Endah; Sumardiyanto, Didit; Setiadi, Novan; J. Rajes Khana (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Electrical energy is energy that is really needed in modern times like now. As the population increases and the economic activity of the population increases, consumption of electrical energy increases. To overcome this problem, namely by creating a power plant with renewable energy, one example is a wave power plant. Wave power plants are plants that rely on wave energy to produce electricity. The aim of this research is to analyze the performance of wave power generators using a buoy system in the coastal area of ​​North Jakarta. By carrying out a total of 10 days of testing in 2 different places, namely Mutiara Beach and Wika Beach, all in North Jakarta. This wave power generator with a buoy system is capable of producing the highest electrical power of 24.9 volts when using a tube-style buoy at Mutiara Beach, while the lowest power is obtained when using a beam-style buoy, namely 6.65 watts at Wika Beach.